Involvement of hypoglossal and recurrent laryngeal nerves on swallowing pressure - Tsujimura, Takanori; Suzuki, Taku; Yoshihara, Midori; Sakai, Shogo; Koshi, Naomi; Ashiga, Hirokazu; Shiraishi, Naru; Tsuji, Kojun; Magara, Jin; Inoue, Makoto (Journal of applied physiology (1985), 2018)
Swallowing pressure generation is important to ensure safe transport of an ingested bolus without aspiration or leaving residue in the pharynx. To clarify the mechanism, we measured swallowing pressure at the oropharynx (OP), upper esophageal sphincter (UES), and cervical esophagus (CE) using a specially designed manometric catheter in anesthetized rats. A swallow, evoked by punctate mechanical stimulation to the larynx, was identified by recording activation of the suprahyoid and thyrohyoid muscles using electromyography (EMG). Areas under the curve of the swallowing pressure at the OP, UES, and CE from two trials indicated high intrasubject reproducibility. Effects of transecting the hypoglossal nerve (12N) and recurrent laryngeal nerve (RLN) on swallowing were investigated. Following bilateral hypoglossal nerve transection (Bi-12Nx), OP pressure was significantly decreased, and time intervals between peaks of thyrohyoid EMG bursts and OP pressure were significantly shorter. Decreased OP pressure and shortened times between peaks of thyrohyoid EMG bursts and OP pressure following Bi-12Nx were significantly increased and longer, respectively, after covering the hard and soft palates with acrylic material. UES pressure was significantly decreased after bilateral RLN transection compared with that before transection. These results suggest that the 12N and RLN play crucial roles in OP and UES pressure during swallowing, respectively. We speculate that covering the palates with a palatal augmentation prosthesis may reverse the reduced swallowing pressure in patients with 12N or tongue damage by the changes of the sensory information and of the contact between the tongue and a palates. NEW & NOTEWORTHY Hypoglossal nerve transection reduced swallowing pressure at the oropharynx. Covering the hard and soft palates with acrylic material may reverse the reduced swallowing function caused by hypoglossal nerve damage. Recurrent laryngeal nerve transection reduced upper esophageal sphincter negative pressure during swallowing.